“Write the world” and tell the stories of your ancestors - Rangiwai, Byron (Te Kaharoa, 2021)
“As we dissect our war history, we discover previously untold or undocumented war stories of many Pacific people who served. Bringing to light these stories will allow a more complete history to be told of our country’s war efforts”.